Seismic protection of unreinforced masonry buildings by means of low cost elastomeric isolation systems. (8th January 2021) - Habieb, Ahmad Basshofi; Milani, Gabriele; Tavio, Tavio; Milani, Federico
Thousands of rural houses in developing countries with high seismicity were built without adequate seismic protection due to economical reason. This paper discusses a possibility to improve the seismic protection of typical unreinforced masonry in developing regions using low cost base isolation devices. The proposed isolation system involves fibre reinforced elastomeric isolators (FREIs) having small dimensions and few layers of rubber pads to reduce the fabrication cost. A series of 3D FE simulations are carried out to investigate the performances of the proposed FREIs utilised in the isolation of a one story masonry house prototype. The model is assumed subjected to several accelerograms to have an insight into the sensitivity of the isolation system against different earthquakes. The results reveal that the proposed low cost FREI system provides significant damage mitigation to the masonry house with good applicability of the FREI devices.